Early childhood education teachers and leaders becoming the leadership(s) - Mettiäinen, Virpi (Reconceptualizing Educational Research Methodology, 2016)
Leadership research in early childhood education (ECE), and in education generally, has been bur-dened with the notion of effectiveness and how this effectiveness relates to the individual leader. Whereas in this paper, the author attempts thinking and becoming leadership assemblage by draw-ing on Mazzei (2013) use of Deleuze and Guattari’s concept of Body/Voice without Organs. As this conceptualization is closely connected to the notions of becoming and temporality, these aspects will also be discussed in this paper. Thinking together with these theoretical concepts, the author has worked with ECE teacher interviews and ECE leader discussions. This conceptualization can offer new understandings of temporality and becoming in educational leadership.